Social Relations and Religious Tolerance among Muslims, Christians, and Hindus in Bugis Village, Sumbawa Regency - Delta Delta (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2025)
This study aims to analyze the forms of social relations between Muslims, Christians, and Hindus in Bugis Village, Sumbawa Regency, and to identify the factors that influence religious harmony. This research employs a qualitative descriptive approach, utilizing a field study and data collection methods that include observation, interviews, and documentation. The findings indicate that social relations between Muslims, Christians, and Hindus in Bugis Village are predominantly associative and harmonious, characterized by tolerance and a strong sense of brotherhood. This tolerance is evident in various community activities, including PKK programs, outreach initiatives, and mutual assistance. However, dissociative patterns also exist, primarily due to competition between the groups. Key factors supporting religious harmony include the active involvement of the community, religious leaders, and the government. Conversely, factors hindering harmony include religious fanaticism, low levels of education, and insufficient communication between religious groups. This study provides valuable insights into the importance of fostering harmonious social relations among different religious communities in Bugis Village.